Draft Sixth Five Year Plan for Major and Medium Irrigation and Flood Control (1978-88) Manipur - Planning Commission (Planning Commission, 1978)
Financial Development - Outlays & Expenditure Five Year Plan 1978-83 Major & Medium Irrigation Project-Benefit & Achievements.
Manipur, Irrigation and Flood Control Department